Cardiac sodium channel inhibition by lamotrigine: In vitro characterization and clinical implications - Lindsey Ingleby‐Talecki; Sven C. vanDijkman; Sean P. Oosterholt; Oscar Della Pasqua; Christina Winter; Marianne Cunnington; Linda Rebar; Sergio Forero‐Schwanhaeuser; Vickas Patel; James A. Cooper; Anthony Bahinski; Khuram W. Chaudhary (Wiley, 2022)
Abstract Lamotrigine, approved for use as an antiseizure medication as well as the treatment of bipolar disorder, inhibits sodium channels in the brain to reduce repetitive neuronal firing and pathological release of glutamate. The shared homology of sodium channels and lack of selectivity associated with channel blocking agents can cause slowing of cardiac conduction and increased proarrhythmic potential. The Vaughan‐Williams classification system differentiates sodium channel blockers using biophysical properties of binding. As such, Class Ib inhibitors, including mexiletine, do not slow cardiac conduction as measured by the electrocardiogram, at therapeutically relevant exposure. Our goal was to characterize the biophysical properties of NaV1.5 block and to support the observed clinical safety of lamotrigine. We used HEK‐293 cells stably expressing the hNaV1.5 channel and voltage clamp electrophysiology to quantify the potency (half‐maximal inhibitory concentration) against peak and late channel current, on‐/off‐rate binding kinetics, voltage‐dependence, and tonic block of the cardiac sodium channel by lamotrigine; and compared to clinically relevant Class Ia (quinidine), Ib (mexiletine), and Ic (flecainide) inhibitors. Lamotrigine blocked peak and late NaV1.5 current at therapeutically relevant exposure, with rapid kinetics and biophysical properties similar to the class Ib inhibitor mexiletine. However, no clinically meaningful prolongation in QRS or PR interval was observed in healthy subjects in a new analysis of a previously reported thorough QT clinical trial (SCA104648). In conclusion, the weak NaV1.5 block and rapid kinetics do not translate into clinically relevant conduction slowing at therapeutic exposure and support the clinical safety of lamotrigine in patients suffering from epilepsy and bipolar disorder.